a Realistic Mathematics Education Model Includes Characteristic to Improve the Skill of Communication Mathematic - Ruswanto, Ruswanto; Dwijanto, Dwijanto; Widowati, Widowati (Unnes Journal of Mathematics Education Research, 2018)
The type of this study is development by using Plomp model with 5 phase that is modified into Preliminary investigation, Design, and realization/ contruction, test, evaluation, and revision. The developed instrumen includes: Syllabus, Lesson Plan, Student Test Book, Worksheet, and Mathematic Communication Skill Test.The field experiment is undertaken to the VII graders students of Al Azhar 23Junior High School Semarang. The data is gained through the observation sheet, interview and test. The result is processed descriptively, using completeness experiment, effect experiment, comparison experiment and development experiment to find out the lesson effectivity.The implementation of this instrumen are (1) the average score of classroom mathematic communication skill of the experimental class students reaching more than the passing grade so the average experimental class is complete, with t = 13.82 > 1.72 = ttable and completely classical, with Z = 2.35 > 1.64 = Ztable, (2) mathematic communication skill, attitude and curiosity effect to mathematic communication skill equal to 89.2%, (3) the experiment of classroom problem solving is better than control class with score 84.86 and 79.9, (4) the average of mathematic communication skill is improved 0.41 so the lesson and the instrumen is efective.